Interventions for Reducing Post-Traumatic Stress Disorder in Intensive Care Unit Survivors: A Scoping Review - Dadan Ramdani; Defa Larashati; Lurdes Acorta Freitas; Nur Azmi Lilikliswati; Suryani Suryani (GLOBAL HEALTH SCIENCE GROUP, 2024)
Post Traumatic Stress Disorder (PTSD) is a serious condition that patients often experience after undergoing intensive treatment in the ICU. Traumatic experiences during ICU care can cause significant and prolonged symptoms. PTSD has a major impact on patients' quality of life after discharge from the ICU. Various literatures have not comprehensively discussed PTSD in ICU survivors. Objective: To explore interventions in reducing PTSD symptoms in ICU survivors. Method: This study used the scoping review method with article searches from three databases, namely CINAHL, PubMed, and Medline. Keywords used included